Upaya Meningkatkan Keaktifan Siswa Melalui Strategi (PBL) Problem Based Learning Berbasis Stad(Student Teams Achievement Division)(PTK Dalam Pembelajaran Matematika Kelas XI Semester Genap SMK Negeri 9 Surakarta Tahun 2014/2015) - Indriastuti, Agustina; , Drs.Arief Wibowo, M.Ag (2015)
This study aimed to increase student activity through strategy-based learning Problem Based Student Teams Achievement Division in class XI Art of SMK Negeri 9 Surakarta. This research is a classroom action research. , Subject recipient action is a class XI Art student of SMK Negeri 9 Art Surakarta totaling 25 students, and the subject of implementing measures is a researcher and teacher of mathematics in class XI Art. Data collection techniques is done by observation, field notes, documentation. To ensure the validity of data used triangulation techniques. The technique of data validity checks done by increasing student activity seen from indicators: (1) Active record material/questions/results of the discussion before action 28% increase 92% by the end of the action. (2) Active answered questions from the teacher before the action 8% increased 44% at the end of the action. (3) Active work on the problems in front of the class before action 4% increased by 48% at the end of the action. (4) Active communication within the group prior to the action 32% increase 88% by the end of the action. (5) Active attention to the teacher's explanation before action 44% increase 88% by the end of the action. From this study it can be concluded that the implementation of Problem Based Learning strategy based Student Teams Achievement Division can enhance the activity of students in the learning of mathematics. Keywords: Learning Math Students activeness, Problem Based Learning, Student Teams Achievement Division.